The effectiveness of school-based child sexual abuse prevention programmes among primary school-aged children: A systematic review - Pinar Celik (International Journal of Educational Research Open)
This systematic review provides a comprehensive overview of child sexual abuse prevalence globally, along with an examination of the effectiveness of school-based prevention education programmes for primary school-aged children. These prevention programmes utilise social cognitive learning theories to teach children the importance of identifying and responding to abusive situations. A total of 676 papers were evaluated with 13 Randomised Controlled Trial (RCT) or cluster RCT design studies identified as meeting the study's inclusion criteria. These studies were published in English between January 2000 and May 2022, and focus on outcomes of school-based prevention programmes designed for primary school-aged children (5–12 years old). To ensure a comprehensive and academically rigorous analysis, the following databases were included: Science Direct, Web of Science, Scopus, the American Psychiatric Association (APA) PsycINFO, Ovid Medline, and Embase. The studies reviewed aim to evaluate the effectiveness of various child sexual abuse prevention programmes in improving children's knowledge and recognition of, and response to potentially unsafe situations. In terms of outcomes and results, the interventions have significantly impacted knowledge, skills, confidence, and awareness in the short and long term. These studies used different intervention methods, including mobile applications, personal safety programmes, and protective behaviour programmes, delivered in various formats such as web-based, textbooks, and in-person sessions. This systematic review highlights the importance of child sexual abuse prevention programmes in schools and the need for further research.